Mesenteric venous thrombosis: A lethal complication of hyperglycemic crises. (29th October 2020) - Tsai, Andrew; Teichman, Amanda; Butts, Christopher A; Cai, Jenny Y; Peck, Gregory L; Adams, Christopher D; Hanna, Joseph S
Abstract: Purpose: Although hyperglycemic crises can lead to a hypercoagulable state, few instances of associated mesenteric venous thrombosis (MVT) have been reported. Worsening abdominal pain in the context of shock requiring vasopressor support should prompt urgent further investigation. Summary: A 44-year-old Hispanic male arrived at an emergency department with chief complaints of lethargy, polydipsia, and polyuria. His past medical history included type 2 diabetes, epilepsy, obesity, tobacco smoking, and noncompliance with his medications. On arrival the patient had a serum glucose concentration of >1, 600 mg/dL, and hyperosmolar hyperglycemic syndrome (HHS) was diagnosed. The patient was admitted to the intensive care unit with respiratory failure and subsequently developed shock refractory to fluid resuscitation, necessitating vasopressor support. On hospital day 4, a computerized tomogram obtained for investigation of increasing abdominal tenderness revealed superior MVT and pneumatosis intestinalis. Despite an emergency laparotomy and enterectomy, the patient ultimately succumbed on hospital day 41 due to recurrent pneumonia complicated by acute respiratory distress syndrome and septic shock. Conclusion: Shock that is refractory to aggressive fluid resuscitation, necessitating pressor support, in the setting of HHS or diabetic ketoacidosis should prompt investigation for the underlying source of shock. Other etiologies, including hypovolemic, cardiogenic, and obstructive shock, should be considered; however, infection is the leading trigger of hyperglycemic crises. Although rarely reported, MVT should be considered in the diagnostic algorithm in the absence of an identified infectious source. Prompt investigation should include use of diagnostic modalities such as computed tomography to assess for MVT.